Revitalisasi Permainan Tradisional Gorontalo sebagai Media Pembelajaran Pendidikan Jasmani Berbasis Kearifan Lokal di SMA Negeri 1 Talaga - Ruslan Ruslan; Ella H Tumaloto; Suriyadi Datau; Sarjan Mile (Universitas Negeri Gorontalo, 2026)
Gorontalo traditional games constitute an important cultural heritage with significant potential to serve as learning media in Physical Education, Sports, and Health (PESH). However, their utilization in schools remains limited, highlighting the need for revitalization efforts to support local wisdom-based learning. This Community Service Program aimed to revitalize two Gorontalo traditional games, Tenggedi Buawu and Ponti, as instructional media for local wisdom-based PESH learning at SMA Negeri 1 Talaga. The program employed a Participatory Action Research (PAR) approach integrated with Service Learning, consisting of preliminary observation, coordination with the school, socialization, training, demonstrations, hands-on practice, mentoring, classroom implementation, and monitoring and evaluation. The participants included PESH teachers and students of SMA Negeri 1 Talaga. The results indicated that teachers improved their knowledge and skills in integrating traditional games into PESH instruction through the development of teaching modules and the implementation of more contextual learning activities. Students demonstrated increased active participation, learning motivation, motor skills, balance, coordination, teamwork, communication, and sportsmanship while participating in Tenggedi Buawu and Ponti. Evaluation findings revealed that the greatest improvement occurred in students' knowledge of traditional games (+49 percentage points), while the highest final achievement was observed in active student participation (95%). Beyond enhancing psychomotor competencies, the program also strengthened the understanding of Gorontalo's local cultural values, including togetherness, mutual cooperation, discipline, responsibility, and cultural heritage preservation. These findings demonstrate that revitalizing Gorontalo traditional games provides an effective, innovative, and contextual alternative for PESH learning. The integration of Tenggedi Buawu and Ponti not only improves the quality of physical education but also supports the implementation of the Merdeka Curriculum by promoting character development, physical literacy, and the preservation of local wisdom. Furthermore, the program has strong potential for replication in other schools as a sustainable culture-based learning strategy.